المساندة الاجتماعية الأسرية وعلاقتها بمستوى الاكتئاب لدى المسنين في دور الرعاية بمحافظة اللاذقية. (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
دفت الدراسة إلى الكشف عن العلاقة بين المساندة الاجتماعية الأسرية والاكتئاب في ضوء بعض المتغيرات لدى عينة من المسنين في دور الرعاية بمحافظة اللاذقية. تكونت العينة من (50) فرداً(30) من الذكور و(20) من الإناث، واستخدم مقياس المساندة الاجتماعية الأسرية المدركة، وقائمة بيك للاكتئاب، وتوصلت الدراسة إلى عدد من النتائج منها،وجود علاقة ارتباطية إيجابية دالة بين درجة المساندة الاجتماعية الأسرية والاكتئاب لدى أفراد عينة الدراسة. ووجود فروق دالة إحصائياً بين الذكور والإناث، في درجة المساندة الاجتماعية الأسرية والاكتئاب، ووجود فروق دالة إحصائياً في درجة المساندة الاجتماعية والاكتئاب لدى أفراد العينة تعزى لمتغير عدد الأولاد. ومما أوصى به البحث: 1. بتفعيل دور الجمعيات الأهلية والمدارس في تقديم المبادرات التطوعية تجاه المسنين. 2. اللجوء إلى طرق تعويضية تحافظ على مستوى مقبول من التواصل بين المسن وأسرته كالتواصل عبر الهاتف أو باستخدام  شبكة النت، مما يعوض ولو جزئياً العجز الحاصل من غياب التواصل المباشر مع الأسرة.The current study aimed at revealing the relationship between family social support and depression of the elderly at infirmaries in Lattakia in the light of some variables. The study was conducted on a sample of 50 individuals: 30 males and 20 females and used the family social support scale and the PIk list of depression. The study came up with a number of results. There is a positive correlation relationship between the level of family social support and depression for the individuals of the sample. There are marked differences statistically between males and females according to the level of family social support and depression. As for the variable of the number of children, there was essential difference on the level of family social support and depression for the individuals in the sample. The study suggested: • activating the role of civil associations in providing the social support for the elderly at  infirmaries.• resorting to compensatory ways to keep an acceptable level of communication between the elderly and their families though telephone, or using cyber communication, which party compensate for the shortfall of the absence of direct communication with the family.